Sistem Informasi Perpustakaan di SMP Swasta Cenderamata Berbasis Web - Br. Tarigan, Emia Edi Ulina Mahdalena; Jamaluddin, Jamaluddin; Harianja, Eva Julia G. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
A computer is a device or machine that works regularly and can handle unwanted things and also functions as a device for processing data. The design and creation of a library information system at Cenderamata Private Middle School is an element that can influence operational tasks at the school. Information that is not fast, inaccurate and inefficient can be resolved by using this system. So that information systems are needed in libraries to support knowledge, insight and information for students and for teachers in schools in supporting the teaching and learning process in schools. In preparing this final project, the author aims to make it easier to borrow books through this computer system so that activities can run smoothly without obstacles due to lack of accuracy. With the system that the author made, problems can be overcome even though they have not reached the expected level of perfection.